Positive discipline - Nelsen, Jane. (New York : Ballantine Books, 2006)
The key to positive discipline is not punishment, Jane Nelsen tells us, but mutual respect. Nelsen coaches parents and teachers to be both firm and kind, so that any child--from a three-year-old toddler to a rebellious teenager--can learn creative cooperation and self-discipline with no loss of dignity.
Foreword --; Preface and acknowledgments --; Introduction to the third edition --; The; Positive approach --; Some basic concepts --; The; Significance of birth order --; A; New look at misbehavior --; Beware of logical consequences --; Focusing on solutions --; Using encouragement effectively --; Class meetings --; Family meetings --; Personality : how yours affects theirs --; Putting it all together --; Love and joy in homes and classrooms --; Appendix I :; Starting a positive discipline study group --; Appendix II :; Developing social responsibility through peer counseling --; Appendix III :; Letter to parents --; Notes --; Suggested readings --; Index.
"Originally published in a different form by Sunrise Press, Fair Oaks, California, in 1981. First revised edition published by Ballantine Books, a division of Random House, Inc., in 1987"--
Includes bibliographical references (p. [335]-342) and index.
Keywords: Discipline of children